Residual disease and HPV persistence after cryotherapy for cervical intraepithelial neoplasia grade 2/3 in HIV-positive women in Kenya. - Hugo De Vuyst; Nelly R Mugo; Silvia Franceschi; Kevin McKenzie; Vanessa Tenet; Julia Njoroge; Farzana S Rana; Samah R Sakr; Peter J F Snijders; Michael H Chung (PLoS ONE)
Objective To assess residual cervical intraepithelial neoplasia (CIN) 2/3 disease and clearance of high-risk (hr) human papillomavirus (HPV) infections at 6 months after cryotherapy among HIV-positive women. Design Follow-up study. Methods 79 HIV-positive women received cryotherapy for CIN2/3 in Nairobi, Kenya, and underwent conventional cytology 6 months later. Biopsies were performed on high grade cytological lesions and hrHPV was assessed before (cervical cells and biopsy) and after cryotherapy (cells). Results At 6 months after cryotherapy CIN2/3 had been eliminated in 61 women (77.2%; 95% Confidence Interval, (CI): 66.4-85.9). 18 women (22.8%) had residual CIN2/3, and all these women had hrHPV at baseline. CD4 count and duration of combination antiretroviral therapy (cART) were not associated with residual CIN2/3. CIN3 instead of CIN2 was the only significant risk factor for residual disease (odds ratio, OR vs CIN2 = 4.3; 95% CI: 1.2-15.0) among hrHPV-positive women after adjustment for age and HPV16 infection. Persistence of hrHPV types previously detected in biopsies was found in 77.5% of women and was associated with residual CIN2/3 (OR = 8.1, 95% CI: 0.9-70). The sensitivity, specificity, and negative predictive value of hrHPV test in detecting residual CIN2/3 were 0.94, 0.36, and 0.96 respectively. Conclusions Nearly one quarter of HIV-positive women had residual CIN2/3 disease at 6 months after cryotherapy, and the majority had persistent hrHPV. CD4 count and cART use were not associated with residual disease or hrHPV persistence. The value of hrHPV testing in the detection of residual CIN2/3 was hampered by a low specificity.